Lessons from patients with hemoptysis attending a chest clinic in India - Prasad Rajendra; Garg Rajiv; Singhal Sanjay; Srivastava Piyush (Annals of Thoracic Medicine, 2009)
Objective:To evaluate the various etiologies of hemoptysis. Materials and Methods: Four hundred and seventy-six consecutive patients of hemoptysis who were admitted to the Department of Pulmonary Medicine between January 1996 and December 2002 were included in this study. Hemoptysis was categorized as mild (< 100 ml/day), moderate (100-400 ml/day), and massive (>400 ml/day). We also categorized the patients according to the primary etiology of the hemoptysis. Results:Of the 476 patients with hemoptysis included in this study, 352 were males and 124 were females. Pulmonary tuberculosis was the leading cause of hemoptysis. There were 377 (79.2%) patients in the pulmonary tuberculosis group, 25 (5.7%) in the neoplasm group, 19 (4.0%) in the chronic bronchitis group, 18 (3.8%) in the bronchiectasis group, and 35 (7.3%) patients with hemoptysis due to other causes. About one-third of the patients with hemoptysis had been misdiagnosed by the referring doctor as having active pulmonary tuberculosis. Conclusion: Although pulmonary tuberculosis is the most important cause of hemoptysis in India, it may also occur due to a variety of other causes. Awareness should be increased among general physicians about the various etiologies of hemoptysis in pulmonary tuberculosis patients.